Triple differential cross section measurements for the outer valence molecular orbitals (1t2) of a methane molecule at 250 eV electron impact. (23rd February 2016) - Işık, N; Doğan, M; Bahçeli, S
Abstract: In this study, detailed experimental research of triple differential cross section (TDCS) measurements is performed to investigate single ionization dynamics for the 1t2 orbital of methane molecule by 250 eV electron impact. In our experiments, the outgoing electrons are simultaneously measured in coincidence in a coplanar asymmetric geometry with the scattering angles of 10° and 20°. Therefore, TDCS measurements are performed for two different values of momentum transfer (K ≈ 0.9 au and 1.5 au). A detailed analysis of the dependence of the TDCS versus the momentum transfer is reported here.